Good Governance between Parliamentary Reform and Partisan Think Tanks - Fadhil, Mohammed (Journal of Legal Sciences, 2022)
The idea of rationalizing parliamentary work tends to reduce the functions of parliament in favor of the government’s authority as a result of its inefficiency in discussing contemporary issues، especially in regimes that suffer from the absence of a political majority and the tendency of parties to achieve their interests. thus making the parliament’s jurisdiction limited to deciding on basic issues such as those related to human rights according to Objective criterion، and the development the legislations of framework . Providing the knowledge needs for MPs helps in achieving a rational debate، and Lawmaking effective through the presence of Research institutions which support the representatives in parliamentary work. Houses of expertise of the parties Bearing a positive impact in terms of the stability of the political majority and the opposition and the balance between them. But its information Bearing unscientific and secretive side، as well as the domination of bureaucratic tendency within the party. It is better to oblige the parties to follow transparency In order for the services of houses of expertise to be known to all، in addition to the Accommodation of periodic programs for seminars and workshops for all members of parliament through legislative expertise houses in important cases So as not to stay the deputy has prisoner of his party’s information.